Adam of Bockenfield, Glossae super de vegetabilibus et plantis : a critical edition with introduction - Long, R. James (Raymond James), 1938- (Studien und Texte zur Geistesgeschichte des Mittelalters ;, 2013)
R. James Long furnishes a critical edition of Adam of Bockenfield's widely influential commentary on the pseudo-Aristotelian treatise on plants, which constituted the set text in university curricula at Oxford as well as Paris by mid-13th century.